2012
DOI: 10.3390/molecules17010843
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Naphthalene Glucosides and an Anthraquinone Isolated from Rumex dentatus and Their Antiproliferation Activities in Four Cell Lines

Abstract: An ethyl acetate extract of the roots of Rumex dentatus L. was investigated. Three compounds were identified by their spectroscopic data as chrysophanol (1), 6-methyl-7-acetyl-1, 8-dihydroxy-3-methoxy naphthalene-1-O-β-D(L)-glucoside (2) and 6-methyl-7-acetyl-1, 8-dihydroxy naphthalene-1-O-β-D(L)-glucoside (3) were found in the plant for the first time. Compounds 2 and 3 are novel compounds. Their antiproliferation activities were tested by the MTT assay in four cell lines (breast cancer MCF-7, gastric cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 7 publications
1
56
1
Order By: Relevance
“…It has antifungal, antibacterial, insecticidal and allelopathic activities Umer et al, 2010). It also showed anti-inflammatory activity (Suleyman et al, 1999), antidermatitis (Litvinenko and MuzychKina, 2003), antiproliferative (Zhang et al, 2012), anthelmintic properties (Bate-Smith, 1962). The paste of plant root is used to relieve headache externally (Manandhar, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It has antifungal, antibacterial, insecticidal and allelopathic activities Umer et al, 2010). It also showed anti-inflammatory activity (Suleyman et al, 1999), antidermatitis (Litvinenko and MuzychKina, 2003), antiproliferative (Zhang et al, 2012), anthelmintic properties (Bate-Smith, 1962). The paste of plant root is used to relieve headache externally (Manandhar, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The genus, comprising more than 250 diverse species, has shown varied biological activity, including anti-inflammatory, antibacterial, antifungal, antiproliferative, and antioxidant activities [17][18][19][20][21][22]. One of these species, Rumex nervosus, is mostly disseminated in the Arabian Peninsula and East Africa.…”
Section: Introductionmentioning
confidence: 99%
“…The spectra also comprises bands for non-oxygenated quaternary carbons (149.4, 121.4, 115.9, 115.8, 113.8 and  133.3) assigned on carbon positions C-3, C-4, C-4 a, C-8 a, C-9 a, C-10 a, for anthraquinone moiety and  133.3 (C-1 ' ) and  133.7 (C-2') positions of phenyl moiety to which methylene hydroxide group is ( 68.2) is linked. From the above data and literatures for anthraquinone moiety (Zhang et al, 2012), the structure of compound 2 (Figure 3) was found to be 4-(2'-oxymethylene-4'-hydroxyphenyl) chrysophanol.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the previous studies, the wide traditional use of the plant may be attributed to its rich anthraquinones, phenolic compounds, flavonoids and resveratrols content. Further work is recommended C NMR spectral data of anthraquinone part of compound 2 and Chrysophanol from literature (Zhang et al, 2012 on various parts of the plant and polar extracts so as to validate the traditional use of the plant and identify more bioactive secondary metabolites in support of its traditional use.…”
Section: Conclusion and Recommendationmentioning
confidence: 99%